Analisis Tingkat Kepuasan Penumpang Terhadap Fasilitas dan Pelayanan di Terminal Tipe A Purabaya Menggunakan Metode Importance Performance Analysis - Panjaitan, Joice Putri Ulina; Sumiati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Service satisfaction is an important aspect of passenger terminals, including Purabaya Type A Terminal. Purabaya Type A Terminal is a passenger terminal with bus services for inter-provincial city transport (AKAP), inter-provincial city transport (AKDP) and city transport. As one of the largest terminals in Southeast Asia, Purabaya Type A Terminal needs to strategically improve passenger satisfaction not only in services but also in facilities based on passenger interest. This study was conducted to improve passenger satisfaction at Purabaya Type A Terminal by prioritising improvements in the services provided by staff and facilities. This analysis of passenger satisfaction was conducted using the Importance Performance Analysis (IPA) method using SPSS Statistics 27 software. There are three attributes that are the main priorities for improvement by Purabaya Type A Terminal, namely, employees are quick in providing information related to entry and exit access, waiting area is spacious and there are many waiting chairs available, and bus arrival times are in accordance with the schedule. It is recommended that Purabaya Type A Terminal prioritise the improvement of the above three attributes as they have a great impact on passenger satisfaction.